ANALYSIS OF EFFECTIVE TAX RATE BASED ON IDX INDUSTRY CLASSIFICATION (IDX-IC) FOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR 2019-2021 - Arya Marantika; Dwi Martani (UNIB Press, 2023)
The aim of this research is to analyze related to the effective tax rate of companies for each classification sector based on the IDX-IC, to analyze the effect of the COVID-19 pandemic on corporate profits and tax burden, and to determine whether the factors used in this study have an influence on the effective tax rate of companies. A purposive sampling technique was used to determine the research sample, which consisted of companies listed on the Indonesia Stock Exchange classified based on the IDX-IC. The research approach used a mixed-methods approach. Based on the research, it was found that the average effective tax rate of the sample companies in 2019-2021 respectively, 26,87%, 24,51%, and 23,83%, with transportation and logistics sector have highest effective tax rate than other sectors. The COVID-19 pandemic has had varying impacts depending on the type of industry. Only the healthcare and infrastructure sector have performed better than other sectors during the COVID-19 pandemic. Apart from the COVID-19 pandemic variable, there are also group company variables used in researching the factors that affect the effective tax rate. Based on the research results, the COVID-19 pandemic variable has a positive effect on the effective tax rate. Meanwhile, group company variables have a negative effect on the effective tax rate. The influence of subsidiary company losses on consolidated profits causes the ratio of the effective tax rate to be smaller than the effective tax rate if it comes from the parent company.